2016
DOI: 10.1016/j.ccell.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Activation Mechanism of Oncogenic Deletion Mutations in BRAF, EGFR, and HER2

Abstract: Activating mutations in protein kinases drive many cancers. While how recurring point mutations affect kinase activity has been described, the effect of in-frame deletions is not well understood. We show that oncogenic deletions within the β3-αC loop of HER2 and BRAF are analogous to the recurrent EGFR exon 19 deletions. We identify pancreatic carcinomas with BRAF deletions mutually exclusive with KRAS mutations. Crystal structures of BRAF deletions reveal the truncated loop restrains αC in an active "in" conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
210
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(235 citation statements)
references
References 43 publications
10
210
0
2
Order By: Relevance
“…Akin to previous publications describing retrospective whole-exome sequencing (7, 9, 10, 24), we found mutations in MAP2K1 and the BRAF V600E point mutation. Additionally, we identified a recurrent novel deletion in BRAF, recently characterized biochemically (Supplemental Figure 2) (21,25). This deletion activates downstream ERK, similarly to BRAF V600E, but is resistant to BRAF V600E inhibitors (21).…”
Section: Discussionmentioning
confidence: 99%
“…Akin to previous publications describing retrospective whole-exome sequencing (7, 9, 10, 24), we found mutations in MAP2K1 and the BRAF V600E point mutation. Additionally, we identified a recurrent novel deletion in BRAF, recently characterized biochemically (Supplemental Figure 2) (21,25). This deletion activates downstream ERK, similarly to BRAF V600E, but is resistant to BRAF V600E inhibitors (21).…”
Section: Discussionmentioning
confidence: 99%
“…Although found infrequently in PDAC (<2%), BRAF -activating V600E mutations were mutually exclusive with KRAS mutations in PDAC (Witkiewicz et al 2015). The widely studied BxPC-3 PDAC cell line, commonly used as a KRAS WT control in comparison with KRAS -mutant cell lines, harbors an in-frame genomic DNA deletion in BRAF that encodes a constitutively activated and transforming BRAF protein with a five-amino-acid deletion (Chen et al 2016; Foster et al 2016). Database analyses found that similar BRAF deletions were found in 4%–5% of KRAS WT PDAC and were mutually exclusive of BRAF missense mutations.…”
Section: Targeting Kras: Do Effector Inhibitors Hold the Greatest Promentioning
confidence: 99%
“…BRAF in-frame deletions do not overlap with KRAS or other BRAF mutations 80 , suggesting that they are sufficient to drive ERK signalling hyperactivation in these tumours. The deletions are mapped within the conserved β3/αC-helix loop of the kinase domain of BRAF, and they are predicted to activate the kinase by shortening the β3/αC-helix loop in a fashion analogous to that of in-frame deletions in epidermal growth factor receptor (EGFR) and HER2 (also known as ERBB2), also found in tumours 12 . This shortening of the β3/αC-helix loop results in a unique conformation that locks the αC-helix in the IN position through the formation of an intact K483-to-E501 salt bridge.…”
Section: Activation Of Mutant Brafmentioning
confidence: 99%
“…This shortening of the β3/αC-helix loop results in a unique conformation that locks the αC-helix in the IN position through the formation of an intact K483-to-E501 salt bridge. Two recent studies focused on the mechanism of activation of in-frame BRAF deletions and their response to RAF inhibitors 12,80 . Chen et al .…”
Section: Activation Of Mutant Brafmentioning
confidence: 99%
See 1 more Smart Citation